Perfil odontológico de pacientes brasileiros com doenças genéticas raras de envolvimento esquelético - Ivanete Cláudia de Oliveira Vilar (2023)
Dental profile of brazilian patients with skeletal rare genetic disorders According to the World Health Organization, a disease is considered rare when it affects about 65 people per 100,000 individuals. Brazil has about 13 million people affected by rare diseases. The aim of the present study was to compare the dental profile of Brazilian patients with skeletal rare genetic disorders and normotypical Brazilian patients. The study was carried out from a database with information collected in 2019. A cross-sectional study was carried out with 105 individuals with rare genetic diseases ([MPS (n=27) / OI (n=78)], with two to 54 years old and their parents/guardians. 105 normotypical individuals were also recruited for the study (Snowball sampling). The sample was selected in outpatient clinics that are reference in the care of rare diseases, in five Brazilian states (Ceará, Espírito Santo, Minas Gerais, Rio de Janeiro and São Paulo). Parents/guardians answered a questionnaire about individual aspects of their child (gender, age, skin color and level of education of parents/guardians).The dental profile was identified from questions related to dental history [(patient’s dental experience, presence of dental pain (last 12 months), when was the last dental visit and the reason for it, use of Unified Health System (SUS) dental care services, satisfaction with the care received at the last dental appointment, difficulties for the child to receive dental treatment)] and presence/absence of dental problems. The study received approval from the Research Ethics Committee of Federal University of Minas Gerais (CAAE 01480212.4.0000.5149 [MPS] / CAAE 54755516.4.0000.5149 [OI]. A descriptive analysis and non-adjusted and adjusted binary logistic regression models was performed (Odds Ratio, Conditional Backward method, 95%CI). The results showed that the average age of individuals with a rare disease was 14.1 years (±12.2) and median age of 9.5 years. Most of them were female (53.8%), non-white skin color (56.7%) and with a family income higher than one minimum wage (82.4%). Among individuals with rare diseases, 78 (37.1) were with OI and 27 (12.9) with MPS. Most of the sample were from Minas Gerais state, Brazil, [98(46.7)]. Participants who had already used SUS dental care services had a 2.24 times higher chance of belonging to the group with rare diseases (OR= 2.24;95% CI: 1.07-4.89). Patients with a history of difficulties to receive dental treatment were 14.86 times more likely to belong to the group with rare diseases (OR=14.86; 95% CI: 5.96-27.03). Patients diagnosed with 1 or more dental problems were 10.38 times more likely to belong to the group with rare diseases (OR=10.38; 95% CI: 1.95-35.17). Individuals with rare diseases have a greater history of difficulty in accessing dental treatment, use the public health system/SUS, and were diagnosed with more dental problems compared to normotypical Brazilian patients.